Mir-132/212 is required for maturation of binocular matching of orientation preference and depth perception - Mazziotti, Raffaele; Baroncelli, Laura; Ceglia, Nicholas; Chelini, Gabriele; Sala, Grazia Della; Magnan, Christophe; Napoli, Debora; Putignano, Elena; Silingardi, Davide; Tola, Jonida; Tognini, Paola; Arthur, J. Simon C.; et al. (Nature communications, 2017)
MicroRNAs (miRNAs) are known to mediate post-transcriptional gene regulation, but their role in postnatal brain development is still poorly explored. We show that the expression of many miRNAs is dramatically regulated during functional maturation of the mouse visual cortex with miR-132/212 family being one of the top upregulated miRNAs. Age-downregulated transcripts are significantly enriched in miR-132/miR-212 putative targets and in genes upregulated in miR-132/212 null mice. At a functional level, miR-132/212 deletion affects development of receptive fields of cortical neurons determining a specific impairment of binocular matching of orientation preference, but leaving orientation and direction selectivity unaltered. This deficit is associated with reduced depth perception in the visual cliff test. Deletion of miR-132/212 from forebrain excitatory neurons replicates the binocular matching deficits. Thus, miR-132/212 family shapes the age-dependent transcriptome of the visual cortex during a specific developmental window resulting in maturation of binocular cortical cells and depth perception. miR-132/212 has been implicated in ocular dominance plasticity during the critical period. Here the authors show that miR-132/212 regulates the expression of genes involved in visual cortex maturation, and that mice lack miR-132/212 show deficits in binocular matching of orientation preferences, which leads to impaired depth perception.